2004
DOI: 10.2739/kurumemedj.51.109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adenosine and ATP on the Membrane Potential and Synaptic Transmission in Neurons of the Rat Locus Coeruleus

Abstract: Effects of adenosine (Ado) and adenosine 5'-triphosphate (ATP) on the membrane potential and synaptic transmission in neurons of the rat locus coeruleus (LC) were examined, in vitro. Ado (30-300 microM) produced a hyperpolarizing response and inhibited spontaneous firing activity in neurons of the rat LC. Ado decreased input resistance of LC neurons. The Ado-induced hyperpolarization reversed polarity near the equilibrium potential of K+ (EK). Ado (100-300 microM) depressed both excitatory postsynaptic potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Hence the pressor response we observed does not appear to be elicited by adenosine. While recent studies have indicated a role for adenosine as well as ATP in synaptic transmission within the LC (Kuwahata, 2004), other similar studies concluded that adenosine was apparently released during hypoxia within the LC. Furthermore, while exogenous adenosine inhibited the spontaneous firing of LC neurones in a slice preparation, antagonism of adenosine receptors had no impact on spontaneous firing but did antagonise the effects of applied adenosine (Nieber et al ., 1995).…”
Section: Discussionmentioning
confidence: 98%
“…Hence the pressor response we observed does not appear to be elicited by adenosine. While recent studies have indicated a role for adenosine as well as ATP in synaptic transmission within the LC (Kuwahata, 2004), other similar studies concluded that adenosine was apparently released during hypoxia within the LC. Furthermore, while exogenous adenosine inhibited the spontaneous firing of LC neurones in a slice preparation, antagonism of adenosine receptors had no impact on spontaneous firing but did antagonise the effects of applied adenosine (Nieber et al ., 1995).…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, Kuwahata (2004) demonstrated that ATP produced a hyperpolarizing response or a transient hyperpolarizing response that preceded the depolarization in LC neurons. However, AMP-PNP (adenosine 5 ′ -(β,γ-imido) triphosphate, which is more resistant to dephosphorylation than ATP, only depolarizes LC neurons.…”
Section: Neurochemical Modulation Of the Lcmentioning
confidence: 98%
“…However, AMP-PNP (adenosine 5 ′ -(β,γ-imido) triphosphate, which is more resistant to dephosphorylation than ATP, only depolarizes LC neurons. According to Kuwahata (2004) adenosine is the likely source of the ATP-induced hyperpolarizing response in LC neurons.…”
Section: Neurochemical Modulation Of the Lcmentioning
confidence: 99%
“…A healthy metabolism also plays a significant role in other higher order processes through its production of adenosine triphosphate (ATP), which, for example, allows the generation of a membrane potential. The membrane potential is itself crucial for a variety of functions, including maintaining the cell's structural integrity and the firing mechanism of neurons (Macknight, 1988;Kuwahata, 2004).…”
Section: Introductionmentioning
confidence: 99%